Sosialisasi Pembukuan Digital, Standarisasi Pelayanan (Kualitas Pelayanan) dan Strategi Pemasaran Digital pada UMKM Kedai Kopi - Zulfa Zakiatul Hidayah; Erin Soleha; Fiqih Maria Rabiatul Hariroh; Rizka Estisia Pratiwi; Laras Hinda Mulia Fadjri (Lembaga Pengembangan Kinerja Dosen, 2026)
Zala Coffee MSMEs have great business potential because they are located in strategic areas, but still face various obstacles in business management, such as manual financial records, the absence of Standard Operating Procedures (SOP) for services, and digital marketing strategies that are not optimal. This Community Service activity aims to improve business management capabilities through socialization of digital bookkeeping, service standardization, and strengthening digital marketing strategies. The implementation method is carried out through five stages, namely socialization and preparation, training, implementation, mentoring and evaluation, and program sustainability. The implementation of activities was carried out face-to-face by involving Zala Coffee owners and staff through the delivery of materials, the practice of using digital bookkeeping applications, the preparation of service SOPs, as well as the optimization of social media and Google Business Profile. The results of the activity show that there is an increase in the understanding and skills of partners in conducting digital-based financial recording, implementing service SOPs more consistently, and utilizing digital media as a means of business promotion. This program has a positive impact on improving the professionalism of business management, operational efficiency, service quality, and expanding marketing reach. Thus, this service activity is expected to support sustainability and increase the competitiveness of Zala Coffee MSMEs in the digital era.